Mechanical and anticorrosive properties of epoxy containing modified graphene Oxide hybrids - Husna, O.N. (Elsevier Ltd, 2019)
The present study investigates the effect of filler loading onto the mechanical and anticorrosive properties of epoxy based polymer nanocomposites. Zinc Oxide nanoparticles decorated graphene oxide (GO-ZnO) hybrids were synthesized with the aid of silane coupling agents and was incorporated as fillers in epoxy. The epoxy nanocomposite were fabricated at different filler loading (0.001 wt, 0.01 wt, 0.1 wt and 0.5 wt). A remarkably low percolation threshold of 0.01 wt is achieved in the GO-ZnO/Epoxy system having the highest tensile strength and Young's Modulus (47 MPa and 30 MPa respectively), compared to bare epoxy that have the lowest tensile strength and Young's Modulus of 24 MPa and 14 MPa respectively. Meanwhile, the protection efficiency of the nanocomposite is the highest at the filler loading percentage of 0.1 wt with a value of 61 after exposed to 3.5 wt NaCl for 14 days. Therefore, the trade-off relationship between the mechanical properties and corrosion protection are discussed. Â© 2019 Elsevier Ltd. All rights reserved.